Cognitive and Motor Outcome in Patients with Early-Detected Central Congenital Hypothyroidism Compared with Siblings - Naafs, Jolanda C (J Clin Endocrinol Metab, 2020)
CONTEXT: Early treatment of primary congenital hypothyroidism (CH) prevents irreversible brain damage. Contrary to primary CH, outcome studies on central CH are scarce. Most patients with central CH have multiple pituitary hormone deficiencies (MPHD); these patients are also at risk for neonatal hypoglycemia. OBJECTIVE: To assess cognitive and motor outcome in patients with early-treated central CH detected by the Dutch neonatal screening. METHODS: In this cross-sectional study, primary outcome full-scale intelligence quotient (FSIQ) was measured in patients with MPHD and patients with isolated central CH born between January 1, 1995, and January 1, 2015, with siblings as controls. Secondary outcomes were intelligence test subscales and motor function. Linear mixed models were used to compare both patient groups and siblings, followed by post hoc tests in case of significant differences. RESULTS: Eighty-seven patients (52 MPHD; 35 isolated central CH) and 52 siblings were included. Estimated marginal means for FSIQ were 90.7 (95% CI 86.4-95.0) in patients with MPHD and 98.2 (95% CI 93.0-103.5) in patients with isolated central CH. While patients with MPHD scored lower FSIQs than siblings (mean difference –7.9 points, 95% CI –13.4 to –2.5; P = .002), patients with isolated central CH did not. Processing speed was lower in both patient groups than in siblings (mean differences –10.5 and –10.3 points). Motor difficulties occurred significantly more often in patients (33%) versus siblings (5%; P = .004). CONCLUSION: In early-treated central CH, FSIQ is comparable with siblings in patients with isolated central CH, while patients with MPHD have a significantly lower FSIQ. This may be explained by disease-specific consequences of MPHD, such as neonatal hypoglycemia and more severe hypothyroidism.